Compliance to mineral supplementation among pregnant women at a public health clinic in Malaysia - Ahmad Fadzil, Nurul Nabilah; Abdul Halain, Azura; Yew Roan Nee, Santhi; Soh, Kim Lam; Japar, Salimah (MA Healthcare, 2021)
Background: Prenatal supplementation has been introduced to pregnant women during early pregnancy to prevent complication to both mother and fetus. The complications include anaemia, postpartum haemorrhage, low birth weight and fetal defects. Aim: To assess compliance with vitamin and mineral supplementation in pregnant women. Methods: A cross-sectional design with simple random sampling was used in this study with 100 respondents who attended the maternal and child clinic in Selangor, Malaysia. Findings: The findings showed that 86 respondents (86%) were compliance towards vitamin and mineral supplementation, whereas 35 respondents (35%) were non-compliance mainly due to forgetfulness. The result indicated a significant association between compliance with race (p=0.02), occupation (p<0.01), household income (p=0.02), education (p<0.01), parity (p<0.01) and trimester (p=0.02). Conclusion: Majority of the respondents acknowledge that side effects and forgetfulness were the main influencing factors towards non-compliance.